The Effect of Entrepreneurial Orientation and Dynamic Capability on the Performance of Ledre MSMEs Structural Equation Modeling (SEM) Approach - Prasetya, Joko Agus; Toiba, Hery; Andriani, Dwi Retno (Universitas Panji Sakti, 2025)
This study aims to evaluate the influence of entrepreneurial orientation and dynamic capabilities on the performance of ledre MSMEs in Bojonegoro Regency. The sample consisted of 72 ledre MSME owners, sampling by simple random sampling with the slovin formula to determine the number. Data analysis techniques using Structural Equation Modeling (SEM). The results showed that entrepreneurial orientation positively and significantly affects dynamic capabilities. This is indicated by the path coefficient value of 0.928 and a P value of 0.000. Dynamic capability has no significant impact on performance; the results of field data processing show a path coefficient value of 0.344 and a P value of 0.116. Entrepreneurial orientation has a positive effect on performance. This is indicated by a path coefficient value of 0.420 and a P value of 0.045. Dynamic capability is not proven to mediate entrepreneurial orientation on performance, this is indicated by a path coefficient value of 0.319 and a P value of 0.117. Suggestions for further research can add other variables that can potentially affect the performance of MSMEs, such as innovation, marketing strategies, or business digitalization.